GAMBARAN DETERMINAN PERILAKU POLA MAKAN KEJADIAN STROKE DIPUSKESMAS DALU SEPULUH TANJUNG MORAWA - Magda Siringoringo; Nagoklan Simbolon; Antonia Kartini Nonseo (Jurnal Online Keperawatan Indonesia, 2022)
Stroke is a symptom that occurs due to impaired blood circulation in the brain.Objective: To find out an overview of the determinants of dietary behavior with stroke events in the dalu ten tanjung morawa health center in 2022.Research Method: using FFQ (Food Frequency Questionnaire). The results showed that 60 respondents at the Dalu Ten Health Center, Tanjung Morawa, with dietary behavior in the type of staple food was sufficient (61.7), the type of meat that had good fat, lacked (55.0), fish and less processing (50.0, enough vegetables and fruit (75.0%), only enough food (55.0%), sufficient food processing (58.3), sufficient and insufficient cooking spices (45.0%), less soft drinks (55.0 ), less dairy products (68.3%). Based on the dietary behavior of stroke patients in consuming staple foods, vegetables and fruit, only food, the food processing of stroke patients is sufficient to understand dietary behavior. Meanwhile, in consuming fatty meats, fish and their processing, cooking spices, and soft drinks, stroke sufferers are still lacking so that the eating behavior of stroke patients must increase food consumption patterns and the need to meet food consumption so that information on eating behavior of stroke sufferers is accurate and correct. Stroke sufferers must regulate their diet and avoid foods that contain high fat and cholesterol, besides that stroke patients are also advised to do physical activity, reduce stress levels by doing activities outside the home, taking vacations, exercising and quitting smoking to prevent stroke